“He’s an idiot!” Experiences of International Students in the United States - Ee, Jongyeon (Journal of International Students, 2013)
Kim, a doctoral student from South Korea, went to a grocery store after being in the U.S. for only one week. When he got to a counter to pay for the items that he picked up, a clerk asked if Kim wanted cash back when he paid with his debit card. Since there was no cash back system in grocery markets in his home country, Kim did not understand right away what the clerk meant. Kim seemed to be puzzled and responded, “Yes, I want cash [back]” but changed his answer in a few seconds, “No, no, no. [I] don’t need [it].” On hearing him, the clerk whispered to another clerk:, “He’s an idiot.”